Inventario de las plantas de tratamiento de aguas residuales Ejército Nacional de Colombia (2014)
The National Army of Colombia is one of the largest state-owned companies in the country, so any activity it carries out is reflected in the society that surrounds them. The National Army must comply with environmental regulations, therefore all its treatments wastewater must meet the efficiency required in the discharge permits. Wastewater Treatment Plants - WWTP play a very important role in the protection of the environment, since its design, operation and proper maintenance minimize the risk of contamination of the wastewater. ecosystems used as a source of wastewater.